Religious Belief as Acquired Second Nature - Eyghen, Hans van ca. 21. Jh. (Zygon, 2020)
Multiple authors in cognitive science of religion (CSR) argue that there is something about the human mind that disposes it to form religious beliefs. The dispositions would result from the internal architecture of the mind. In this article, I will argue that this disposition can be explained by various forms of (cultural) learning and not by the internal architecture of the mind. For my argument, I draw on new developments in predictive processing. I argue that CSR theories argue for the naturalness of religious belief in at least three ways; religious beliefs are adaptive; religious beliefs are the product of cognitive biases; and religious beliefs are the product of content biases. I argue that all three ideas can be integrated in a predictive coding framework where religious belief is learned and hence not caused by the internal architecture of the mind. I argue that the framework makes it doubtful that there are modular cognitive mechanisms for religious beliefs and that the human mind has a fixed proneness for religious belief. I also argue that a predictive coding framework can incorporate a larger role for cultural processes and allows for more flexibility.